Replantation of en-bloc amputation of all five toes: A very rare case - Ghosh, Abhishek; R, Jayakumar (Indian Journal of Case Reports, 2019)
Loss of all toes not only causes tremendous psychological impact but also causes a significant functional defect. There is no reported case of replantation ofen bloc amputation of all five toes and very few papers on single or double toe replantations hence we had to rely on our experiences and logic to salvage the amputated part. Here, we report the case of replantation of en-bloc amputation of all five toes in a 16-year-old male. The purpose of this report is to share the authors’ experience with en bloc toe replantation. Successful replantation goes a long way in mitigating the psychological and functional trauma of the patient.